2013
DOI: 10.21121/eab.2013119496
|View full text |Cite
|
Sign up to set email alerts
|

Örgütsel Vatandaşlık Davranışının İş Performansı ve İşten Ayrılma Niyeti Üzerine Etkisinde Aşırı İş Yükünün Aracılık Rolü

Abstract: Yüksek ve küresel rekabet ortamında işletmeler rakiplerine üstünlük sağlayarak ayakta kalma mücadelesi vermektedirler. Bu mücadelede başarılı olmanın en önemli şartlarından bir tanesi de, çalışanların güçlerinden ve yeteneklerinden azami fayda sağlayabilmektir. Bu kapsamda örgütsel vatandaşlık davranışı (ÖVD), çalışanların işletmeye olan katkılarının biçimsel rollerinin ötesine geçtiği önemli bir davranış biçimidir. Organ (1983), ÖVD'yi "biçimsel ödül sisteminde doğrudan ve tam olarak dikkate alınmayan, fakat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 10 publications
0
4
0
6
Order By: Relevance
“…Thus, H4 was accepted, but H5 was rejected. These results were supported by Ahmad et al, 2010;Çelik and Çıra, 2013;Demirel and Özçınar, 2009;Paillé and Grima, 2011. According to the results of regression analyzes, it was maintained that organizational citizenship behavior was a partial mediator in the organizational commitment and job satisfaction relationship. Nevertheless, it has no mediator role on the relationship between organizational commitment and intention to leave.…”
mentioning
confidence: 63%
“…Thus, H4 was accepted, but H5 was rejected. These results were supported by Ahmad et al, 2010;Çelik and Çıra, 2013;Demirel and Özçınar, 2009;Paillé and Grima, 2011. According to the results of regression analyzes, it was maintained that organizational citizenship behavior was a partial mediator in the organizational commitment and job satisfaction relationship. Nevertheless, it has no mediator role on the relationship between organizational commitment and intention to leave.…”
mentioning
confidence: 63%
“…Bu araştırmada, ölçeğin orijinaline uygun olarak öğrenilmiş güçlülük ölçeği tek boyut olarak kullanılmıştır. Rosenbaum'un (1980) geliştirdiği öğrenilmiş güçlülük ölçeği, yerli ve yabancı literatürde çok sayıda araştırmada tercih edilmiştir (Örneğin; Kennett & Keefer, 2006;Yürür & Keser, 2010;Özdemir, 2015;Chen vd., 2015;Topçu & Yücekaya, 2017 Tutar & Altınöz, 2010;Çelik & Çıra, 2013;Yılmaz, 2016).…”
Section: Veri Toplama Yöntemi Ve Araçlarıunclassified
“…When the literature was reviewed, the studies examining the relation between intention to quit and the performance share the finding of significant and negative correlation between two variables (Tuten and Neidermeyer, 2004;Zimmerman and Darnold, 2009;Çelik and Çıra, 2013;Begenirbaş and Çalışkan, 2014 ;Fabi et al, 2015). There was only one study examining the relation between work engagement and intention to quit, and performance (Halbesleben and Wheeler, 2008); this study found out that the intention to quit had a significant and negative relation with the other two variables whereas there was a significant and positive relationship between work engagement and job satisfaction.…”
Section: Job Performancementioning
confidence: 99%